Wojenne i powojenne losy językoznawców wileńskich - Bednarczuk, Leszek (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2013)
The author focuses, after brief outline of wartime highlights in the life of Professor Zygmunt Zagórski, on short biographical notes of prewar linguists from Wilno, who after the war moved to various research centres in Poland and abroad: Olgierd Chomiński, Jan Otrębski, Erwin Koschmieder, Halina Turska, Józef Trypućko, Czesław Kudzinowski, Wacław Cimochowski, Antoni Szantyr, Zofia Abramowiczówna, Stefan Oświęcimski, Danuta Turkowski, Anatol Mirowicz, Max Weinreich, Stanisław Stankiewicz. Additionally, there are discussions of several scientists who approached linguistics in their research: Kazimierz Moszyński, Konrad Górski, Maria Renata Mayenowa, Maria Aleksandra Rzeuska, Czesław Zgorzelski, Józef Bujnowski. The article concludes with an reprint of a poem by Józef Bujnowski, written on hearing the news of disarmament of the Armia Krajowa resistance army.